P-cadherin expression in breast cancer: a review - Paredes, Joana (2007)
P-cadherin is frequently over-expressed in high-grade invasive breast carcinomas and has been reported to be an enhancer of migration and invasion of breast cancer cells, being correlated with tumour aggressiveness. In addition, expression of P-cadherin is well established as an indicator of poor prognosis in human breast cancer, which has stimulated our interest in studying its role in this setting. This review describes the most important findings on P-cadherin expression and function in normal mammary tissue and breast cancer cells, emphasizing that further research is required to elucidate the role played by this protein in human mammary tumours.